A Review of Integration of Engineering Design Process (EDP) Learning Model through STEM Approach in Elementary Schools - Sutisnawati, Astri; Rahmawati, Yuli; Sumantri, Mohamad Syarif; Lestari, Ika (EduBasic Journal: Jurnal Pendidikan Dasar, 2025)
This study reviews the learning of the Engineering Design Process (EDP) with the Science, Technology, Engineering, and Mathematics (STEM) approach that is operationalised. The review summarised and evaluated research articles published between 2014 and 2024, which specifically focus on the integration of EDP learning models with STEM approaches. This study uses the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) framework and follows the CRAAP Test, an evaluation tool used to assess the reliability, relevance, and credibility of the selected paper. After a rigorous search and selection process, 28 unique empirical studies were identified that explored the integration of EDP models with STEM approaches at various levels of education, from elementary school to college. The review revealed that there are only three topics that are suitable for integrating EDP learning models with STEM approaches in elementary schools. Limited research exists about the adaptability, obstacles, and support of STEM-based EDP implementation in primary schools, focusing mostly on identification rather than in-depth studies. In addition, various instruments can be leveraged to facilitate the integration of EDP-STEM learning models in primary education. This result found a gap for further research on STEM-based EDP in elementary schools as a trend of scientific contribution related to the use of STEM-based education in elementary schools.